2016
DOI: 10.1186/s12931-016-0356-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of lung function and St. George's respiratory questionnaire with exacerbations in COPD: a systematic literature review and regression analysis

Abstract: BackgroundThis study investigated the relationship between changes in lung function (as measured by forced expiratory volume in one second [FEV1]) and the St. George’s Respiratory Questionnaire (SGRQ) and economically significant outcomes of exacerbations and health resource utilization, with an aim to provide insight into whether the effects of COPD treatment on lung function and health status relate to a reduced risk for exacerbations.MethodsA systematic literature review was conducted in MEDLINE, Embase, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 33 publications
3
27
0
1
Order By: Relevance
“…And 20% of these patients were hospitalized within the next year due to exacerbation. These findings confirm the previous studies which showed that exacerbation risk correlates with FEV 1 …”
Section: Discussionsupporting
confidence: 92%
“…And 20% of these patients were hospitalized within the next year due to exacerbation. These findings confirm the previous studies which showed that exacerbation risk correlates with FEV 1 …”
Section: Discussionsupporting
confidence: 92%
“…ICS had a protective effect on all individual CID components, indicating that the benefit offered by BUD extends beyond the effect on exacerbations, and includes prevention of deteriorations in lung function and QoL. This contrasts with the modest effect of ICS when assessing improvements in FEV 1 and SGRQ previously reported with ICS [13], suggesting that ICS in COPD are primarily preventive and protective, rather than to induce improvements in lung function and QoL only. Patients who experienced a CID within Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, patients should be monitored until they have fully recovered from their COPD exacerbation [49]. While a long symptom duration during a COPD exacerbation was associated with an increased risk of further exacerbations [45], a fast recovery in lung function following treatment has been shown to be significantly associated with a lower risk for COPD exacerbations [50].…”
Section: Effect On Lung Functionmentioning
confidence: 99%
“…However, even a mild COPD exacerbation can adversely impact patient health-related quality of life [53]. Conversely, a better health-related quality of life has been associated with a lower risk for COPD exacerbations [50].…”
Section: Effect On Quality Of Life and Physical Activitymentioning
confidence: 99%